Food insecurity in ACP countries: from policy and programme interventions to vulnerable groups - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Seminar summary report, Leuven, Belgium, 1998CTA, 1999, 27pp,ISBN 92 9081 2141 CTA No. 946. 5 credit points